TEACHING ENGLISH IN RURAL SCHOOLS: STRATEGIES AND BARRIERS IN ACEH SINGKIL REGENCY - Nofreza Setia Geby R; Syahputra, Mulyadi; Miftahul Fahmi, Said (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore English teaching strategies and the obstacles faced by teachers in rural secondary schools in Aceh Singkil Regency. The study uses a qualitative approach with a multiple case study design, involving three English teachers from three different schools as participants. Data were collected through classroom observations and in-depth interviews, then analyzed thematically. The results showed that teachers applied flexible and adaptive teaching strategies, combining teacher-centered and student-centered approaches, using various learning models such as Discovery Learning, Direct Instruction, and Cooperative Learning, as well as varied learning methods, techniques, and media. This approach helped teachers tailor learning to students' abilities and needs, as well as limited classroom conditions. However, there were several obstacles that affected the effectiveness of learning, including limited facilities, minimal learning resources, challenges in developing teacher competencies, and low student motivation and participation. These obstacles underscore the importance of institutional and government support to improve infrastructure, provide learning resources, and enhance professional training for teachers. This study makes an important contribution to understanding English language teaching practices in rural contexts and shows how teachers can adapt in limited conditions. The results of this study can also serve as a reference for educators, researchers, and policymakers in designing more effective learning strategies in rural schools.